Analisis Hubungan Service Recovery terhadap Complaining Behavior dan Dampaknya terhadap Brand Switching - Dian Tauriana; Christine Christine (Binus Business Review, 2011)
PT Bank OCBC NISP Tbk officially became a commercial bank in 1967, foreign exchange bank in 1990, and listed as a public company in Indonesia Stock Exchange in 1994. The purpose of this research is to identify the correlation and variables influences of service recovery, complaining behaviour, and brand switching; and also to give suggestion of extensive complaint handling so the customers of PT Bank OCBC NISP Tbk are more loyal. The analysis method is SPSS 16.00 program, simple correlation, and path analysis. Data collecting technique is questionnaire, as the amount of respondents (customers) are 100. The result of this research is there is relation and influences among service recovery, complaining behaviour, and brand switching variables.